OUTCOME OF DYNAMIC COMPRESSION PLATE WITH DORSAL RADIAL SLIDING GRAFT TECHNIQUE FOR WRIST ARTHRODESIS IN BRACHIAL PLEXUS INJURY PATIENTS - Ivalde, Flavio César; Marazita-Valverde, José; Bataglia, Danilo (Journal of Ayub Medical College Abbottabad, 2019)
We have meticulously read the article titled "Outcome of dynamic compression plate with dorsal radial sliding graft technique for wrist arthrodesis in brachial plexus injury patients". We would like to comment on some aspects of the study and set forth our experience in wrist arthrodesis performed to improve functional outcome in the scenarios cited above. This manuscript aims to highlight the following. First, to the best of our knowledge, there exists a paucity of comparative studies on the use of a reamer/iliac crest /radial sliding graft for total wrist arthrodesis, evaluating fusion times and complications. Second, we propose adult traumatic brachial plexus injury involves injury -particularly of the C7-C8-T1 root injury- as an indication for metacarpophalangeal arthrodesis along with wrist fusion to provide stability of thumb grasp. Third, there is no consensus on the selection criteria for metacarpophalangeal arthrodesis in patients with plexopathy, in order to improve the stability of the hand and thereby improving the activities of daily life. Long-term functional outcome follow-up and patient satisfaction over an extended time frame may also be valuable for future studies to consider. Keywords: Brachial plexus Palsy; bone deformity; Humeral retroversion; Surgical Planning